Quality of life and burden in family caregivers of patients with advanced cancer in active treatment settings and hospice care: A comparative study. Issue 5 (28th May 2017) - Spatuzzi, Roberta; Giulietti, Maria Velia; Ricciuti, Marcello; Merico, Fabiana; Meloni, Cristina; Fabbietti, Paolo; Ottaviani, Marica; Violani, Cristiano; Cormio, Claudia; Vespa, Anna
ABSTRACT: The aim of this study was to evaluate caregiver burden and quality of life (QoL) in active treatment settings and hospice care for 76 family caregivers of advanced cancer patients, using the Medical Outcomes Study Short Form and the Caregiver Burden Inventory. Compared to the active group, the hospice group reported significantly lower QoL scores in mental component summary score and higher scores in general health subscale and in physical component summary score. Future research needs to further investigate the complexities of caregivers' needs, especially in the emotional and mental domains, and offer effective, clinically proven interventions.